A 20-week, randomized controlled trial to determine the efficacy of the Aging Well through Interaction and Scientific Education – Action Plan (AgeWISE-AP) program in older Veterans - Maureen K. O’Connor; Julianne Szemko; Jaye E. McLaren; Lauren R. Moo; Emily E. Metcalf; Andrew Nguyen; Malissa L. Kraft; Brandon Frank; David Salat; John J. Randolph; Yorghos Tripodis (BMC Geriatrics)
Abstract Background Advancing age is the number one risk factor for cognitive decline and dementia, making cognitive aging a concern for the nearly half of Veterans who are age 65 and older. There has been a growing appreciation for the value of nonpharmacological lifestyle interventions in dementia risk reduction, including consistently exercising, eating a healthy diet, getting sufficient sleep, socializing, and engaging in cognitively stimulating activities. The 12-week Aging Well through Interaction and Scientific Education program (AgeWISE) provides Veterans with education about brain aging and modifiable lifestyle factors that promote cognitive resilience. A pilot study conducted in 2013 revealed modest improvements in AgeWISE participants’ perceived ability to control brain aging. Methods The recently funded AgeWISE-Action Plan (AgeWISE-AP) aims to capitalize on the increased feelings of control over brain aging found in the AgeWISE program through the addition of an action plan (AP) component. The AP involves 8 individualized sessions with a Brain Health Interventionist in addition to AgeWISE group participation. A total of 128 Veterans will be enrolled in the study and each will be randomized to one of the two study arms: AgeWISE-AP (intervention arm) or a no treatment control condition. Outcome measures will be administered at baseline (pre-intervention), immediately post-intervention, and 3- and 6-months post-intervention. These outcome measures assess engagement in brain-healthy lifestyle factors, psychological well-being, and cognition. Linear mixed regression models will be used to test the effect of AgeWISE-AP. An exploratory outcome will focus on structural imaging data acquired from a subset of participants at baseline and one year to investigate potential volumetric changes in brain regions of interest. Discussion Multi-component interventions that provide brain aging education, improve feelings of control over brain aging, and deliver practical assistance with goal setting and attainment are critically needed to improve cognitive outcomes for older adults. The AgeWISE-AP program aims to increase engagement in protective lifestyle factors, and directly target and improve psychological wellbeing and cognition in older Veterans. Trial registration This study was registered with ClinicalTrials.gov (NCT06006962) on August 17, 2023.